Simple Student Grades Analytics Dashboards in Higher Education in Vietnam - Thanh, Truong Ba; TD, Dang; Le, Doan Hong; Jr., Perfecto G. Aquino (The journal of contemporary issues in business and government, 2021)
In the higher education environment, tracking and analyzing student learning outcomes by subject is one approach to improving student learning outcomes in the next subjects. Large universities using the course management system could provide stakeholders with comprehensive assessments and data to review and assess student learning outcomes. There seems to be little such research at small- and medium institutions, in any case. This research suggests a simple method to design a dashboard that can be used by faculty and other university stakeholders to evaluate the learning outcomes of each subject. By using the information from the dashboards, useful advice and assistance are given to students. The most significant of this study is demonstrated a simple method to creating a meaningful dashboard. A score sheet is a unique input, and any faculty or staff can do it. A case study on a university in Vietnam also uses to illustrate management implications and development direction.